Weighing in on the average weights: measuring corporate social performance (CSP) score using DEA - Chen, Chien-Ming (2024)
This study develops a new DEA approach to incorporate such market-level information (i.e., average weights over firms) to create a composite corporate social performance (CSP) measure. The new model addresses the challenge that stakeholder expectations—expressed as the CSP weights of different CSP dimensions—are usually unknown at the firm level, but some reliable estimates of the average weights (across firms) are available at the industry or market level. Distinct from the traditional DEA, the new approach can incorporate constraints on the average values of weight distributions and is built on a computational framework new to the literature. The new model is compared with the traditional CSP approach, using longitudinal investment data by socially responsible funds (SRF). The regression results show evidence that the traditional CSP score, which is widely used in the management literature, may not be a reliable CSP score: firms with higher CSP scores tend to have lower SRF investment (in both the number of SRF and total shares). In contrast, the DEA-based CSP scores show the correct and positive correlation with SRF investment. Overall, this paper contributes to the literature by presenting a more reliable CSP approach and a new, generalizable DEA model. This is also the first empirical work documenting the potential validity issue of the traditional CSP scores.